Secreted Amyloid Precursor Protein-Alpha Promotes Arc Protein Synthesis in Hippocampal Neurons - Livingstone, Rhys W.; Elder, Megan K.; Barrett, Maya C.; Westlake, Courteney M.; Peppercorn, Katie; Tate, Warren P.; Abraham, Wickliffe C.; Williams, Joanna M. (Frontiers in Molecular Neuroscience, 2019)
Secreted amyloid precursor protein-α (sAPPα) is a neuroprotective and memory-enhancing molecule, however the mechanisms through which sAPPα promotes these effects are not well understood. Recently, we have shown that sAPPα enhances cell-surface expression of glutamate receptors. Activity-related cytoskeletal-associated protein Arc (Arg3.1) is an immediate early gene capable of modulating long-term potentiation, long-term depression and homeostatic plasticity through regulation of α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor localization. Accordingly, we hypothesized that sAPPα may enhance synaptic plasticity, in part, by the de novo synthesis of Arc. Using primary cortical and hippocampal neuronal cultures we found that sAPPα (1 nM, 2 h) enhances levels of Arc mRNA and protein. Arc protein levels were increased in both the neuronal somata and dendrites in a Ca2+/calmodulin-dependent protein kinase II-dependent manner. Additionally, dendritic Arc expression was dependent upon activation of mitogen-activated protein kinase and protein kinase G. The enhancement of dendritic Arc protein was significantly reduced by antagonism of N-methyl-D-aspartate (NMDA) and nicotinic acetylcholine (α7nACh) receptors, and fully eliminated by dual application of these antagonists. This effect was further corroborated in area CA1 of acute hippocampal slices. These data suggest sAPPα-regulated plasticity within hippocampal neurons is mediated by cooperation of NMDA and α7nACh receptors to engage a cascade of signal transduction molecules to enhance the transcription and translation of Arc.